Biodiversity and species identity shape the antifungal activity of bacterial communities. Issue 5 (1st May 2014) - Jousset, Alexandre; Becker, Joachim; Chatterjee, Subhankar; Karlovsky, Petr; Scheu, Stefan; Eisenhauer, Nico
Abstract : Soils host diverse communities of interacting microbes and the nature of interspecific interactions is increasingly recognized to affect ecosystem‐level processes. Antagonistic interactions between bacteria and fungi are of particular relevance for soil functioning. A number of soil bacteria produce secondary metabolites that inhibit eukaryotic growth. Antibiosis may be stimulated in the presence of competing bacteria, and we tested if biodiversity within bacterial communities affects their antagonistic activity against fungi and fungal‐like species. We set up Pseudomonas communities of increasing diversity and measured the production of the broad spectrum antifungal compound 2, 4‐DAPG and their antagonistic activity against different eukaryotes. Diversity increased DAPG concentration and antifungal activity, an effect due to a combination of identity and interactions between species. Our results indicate that investment of pseudomonads into broad spectrum anti‐eukaryotic traits is determined by both community composition and diversity and this provides new avenues to understand interactions between bacterial and fungal communities.